Psychiatric morbidity among pregnant and non pregnant women in Ibadan, Nigeria - Oluwasomidoyin Olukemi Bello; Tolulope T. Bella-Awusah; Ayodeji Matthew Adebayo; Yetunde O. John-Akinola; Chizoma Milicent Ndikom; Temitope Ilori; Eniola O. Cadmus; Folashade Omokhodion (Taylor & Francis Group, 2023)
A comparative cross-sectional study was conducted among 991 pregnant and 674 non-pregnant women of reproductive age attending healthcare facilities in Ibadan, Nigeria using the General Health Questionnaire-12 (GHQ), and WHO self-reporting questionnaire (SRQ). Logistic regression analysis was conducted to identify predictors of psychiatric morbidity at p < 0.05. A significantly higher proportion of pregnant women experienced psychological distress on the GHQ (51.8%) and psychiatric morbidity on SRQ (33.3%) compared with 28.6% and 18.2% of non-pregnant women, respectively. Predictors of psychiatric morbidity among pregnant women were the type of facility, poor satisfaction and communication with partners, the experience of violence in the home, previous abortions, and previous history of depression. Psychiatric morbidity among non-pregnant women was predicted by younger age, previous history of depression, poor satisfaction and communication with partners. There is a need for early identification of psychiatric morbidity among women of reproductive age, to ensure early interventions and prevent long-term disability.Impact statement What is already known on this subject? Psychiatric morbidity has immense effects on a woman's quality of life, social functioning, obstetric outcome, and economic productivity. What do the results of this study add? Psychiatric morbidity among women of reproductive age is high. Pregnant women when compared to non-pregnant women had significantly higher rates of psychiatric morbidity. This high prevalence of psychiatric morbidity in both groups was predicted by poor satisfaction and communication with partners, and a previous history of depression. What are the implications of these findings for clinical practice and/or further research? Simple screening for women of reproductive age attending healthcare facilities may help with the early identification of psychiatric morbidity leading to prompt interventions, and preventing long-term disability.